Relationship between aspartate aminotransferase to platelet ratio index and liver injury in pediatric sepsis - Robby Godlief; Dzulfikar Djalil Lukmanul Hakim; Dwi Prasetyo (Paediatrica Indonesiana, 2021)
Background Sepsis-associated liver injury (SALI) is one of the main clinical manifestations of sepsis, as well as an independent risk factor for multiple organ dysfunction syndrome and mortality in pediatric sepsis. The early warning biomarkers for identifying SALI remain poorly defined. Objective To analyze the relationship between aspartate aminotransferase to platelet ratio index (APRi) and liver injury occurrence in pediatric sepsis, as well as determine the APRi cutoff value for early identification of SALI. Methods This retrospective study used secondary data derived from January 2019 to August 2020. The study population comprised admitted children aged 1 month to <18 years who met the criteria for sepsis, and had aspartate aminotransferase (AST) and platelet laboratory parameters checked in the first 24 hours of sepsis and before administration of antibiotics. Pearson’s Chi-square test was used to analyze for correlations. Estimation of the APRi cutoff value in the early occurrence of SALI was performed with logistic regression analysis and receiver operating characteristic (ROC) curve. Results Of the 112 subjects, 94.6% were categorized as having septic shock and 48.2% had SALI. Logistic regression revealed that APRi was a significant predictor of SALI, as indicated by cut-off 4.726 [OR 1.098; 95%CI 1.002 to1.203; P=0.045]. The area under the curve (AUC) was 0.831 or 83.1%, which was classified as strong (80-90%). Conclusion The APRi is a reliable early predictor of SALI in pediatric sepsis, as indicated by an increase in APRi (> 4.726) within the first 24 hours of sepsis.